Matematyka
szalonytatusiek
2017-06-25 09:20:07
oblicz zad 18 a 2/3-1/2:3/4-2/3 b 6/5-2/7:2/5+2/3 c 1 1/2-2,75:1 5/6-2 1/2 d 1,25+27/8: 1 5/16+3/8 e 1 5/6-0,625:4/13-25/39
Odpowiedź
szlonaaaaa
2017-06-25 13:58:48

a) [latex] frac{2}{3} - frac{1}{2} : frac{3}{4} - frac{2}{3} = frac{4}{6}- frac{3}{6} : frac{9}{12} - frac{8}{12} = frac{1}{ ot6_{1}} * frac{ ot12^{2}}{1} = 2 [/latex] b) [latex] frac{6}{5}- frac{2}{7}: frac{2}{5}+ frac{2}{3} = frac{42}{35}- frac{10}{35} : frac{6}{15}+ frac{10}{15}= frac{32}{35} : frac{16}{15} = frac{^{2} ot32}{ ot35_{7}} * frac{ ot15^{3}}{ ot16_{1}}= frac{6}{7} [/latex] c) [latex]1 frac{1}{2}-2,75:1 frac{5}{6}-2 frac{1}{2}= frac{3}{2}-2 frac{3}{4}: frac{11}{6}- frac{5}{2}= frac{3}{2}- frac{11}{4}: frac{11}{6}- frac{5}{2}= frac{6}{4}- frac{11}{4}: frac{11}{6} [/latex][latex]- frac{15}{6}=(- frac{5}{4}):(- frac{4}{6})= (- frac{5}{ ot4_{1}})*(- frac{ ot4^{1}}{6})= frac{5}{6}[/latex] d)[latex]1,25+ frac{27}{8}:1 frac{5}{6}+ frac{3}{8}=1 frac{1}{4}+ frac{27}{8} : frac{21}{16}+ frac{3}{8}= frac{5}{4}+ frac{27}{8}: frac{21}{16}+ frac{3}{8}= frac{10}{8}+ frac{27}{8}: frac{21}{16} [/latex] [latex]+ frac{6}{16}= frac{37}{8}: frac{27}{16} = frac{37}{ ot8_{1}} * frac{ ot16^{2}}{27}= frac{74}{27} = 2 frac{20}{27} [/latex] e)[latex]1 frac{5}{6} - 0,625: frac{4}{13}- frac{25}{39}= frac{11}{6}- frac{5}{8}: frac{4}{13} - frac{25}{39} = frac{44}{24}- frac{15}{24} : frac{12}{39}- frac{25}{39}= frac{29}{24}:(- frac{13}{39}[/latex][latex]= frac{29}{24}*(- frac{ ot39^{3}}{ ot13_{1}}) = frac{29}{ ot24_{8}}*(- frac{ ot3^{1}}{1}) = - frac{29}{8}=-3 frac{5}{8} [/latex]

patrysia1327
2017-06-25 14:00:03

zad 18 a) 2/3-1/2:3/4-2/3 = = 2/3 - 1/2 * 4/3 - 2/3= = 2/3 - 1/1 * 2/3 - 2/3= = 2/3 - 2/3 - 2/3= = 0 - 2/3 = = - 2/3 b)   6/5-2/7:2/5+2/3= = 6/5 - 2/7 * 5/2 + 2/3= = 6/5 - 1/7 * 5/1 + 2/3= = 6/5 - 5/7 + 2/3= = 42/35 - 25/35 + 2/3 = = 7/35 + 2/3= = 1/5 + 2/3= = 3/15 + 10/15= = 13/15 c) 1 i 1/2-2,75:1 i 5/6-2 i 1/2 = = 1 i 1/2 - 2 i 75/100 : 11/6 - 2 i 1/2= = 1 i 1/2 - 2 i 3/4 : 11/6 - 2 i 1/2= = 1 i 1/2 - 11/4 * 6/11 - 2 i 1/2= = 1 i 1/2 - 1/2 * 3/1 - 2 i 1/2= = 1 i 1/2 - 3/2 - 2 i 1/2= = 1 i 1/2 - 1 i 1/2 - 2 i 1/2= = 0 - 2 i 1/2 = = - 2 i 1/2 d) 1,25+27/8: 1 i 5/16+3/8 = = 1 i 25/100 + 27/8 : 21/16 + 3/8= = 1 i 1/4 + 27/8 * 16/21 + 3/8= = 1 i 1/4 + 9/1 * 2/7 + 3/8= = 1 i 1/4 + 18/7 + 3/8= = 1 i 1/4 + 2 i 4/7 + 3/8= = 1 i 14/56 + 2 i 32/56 + 21/56= = 3 i 46/56 + 21/56= = 3 i 67/56= = 4 i 11/56 e ) 1 i 5/6-0,625:4/13-25/39 = = 1 i 5/6 - 625/1000 * 13/4 - 25/39= = 1 i 5/6 - 5/8 * 13/4 - 25/39= = 1 i 5/6 - 65/32 - 25/39= = 1 i 5/6 - 2 i 1/32 - 25/39= = 1 i 80/96 - 2 i 3/96 - 25/39 = = - 19/96 - 25/39 = = - 247/1248 - 800/1248= = - 1047/1248= = - 349/416

Dodaj swoją odpowiedź